2012
DOI: 10.1007/s00396-012-2630-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and micellar characterization of thermosensitive amphiphilic poly(ε-caprolactone)-b-poly(N-vinylcaprolactam) block copolymers

Abstract: Poly(ε-caprolactone)-b-poly(N-vinylcaprolactam) (PCL-b-PVCL) block copolymers were synthesized as new biocompatible, thermosensitive, amphiphilic block polymers by a combination of ring-opening polymerization and reversible addition-fragmentation chain transfer (RAFT) polymerization, and their thermosensitive micellar behavior was examined. The PCL macro-chain-transfer agent was first synthesized by converting the end group of PCL-OH to O-ethyl xanthate, which was subsequently used for the RAFT polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 21 publications
(29 reference statements)
1
44
0
3
Order By: Relevance
“…Only a few CRP techniques can properly mediate the radical polymerization of NVCL, including reversible additionfragmentation chain transfer (RAFT) [16][17][18][19][88][89][90][91][92][93][94][95], a combination of ring-opening polymerization (ROP) and RAFT [96,97], atom transfer radical polymerization (ATRP) [98], and Cobalt mediated radical polymerization (CMRP) [20,29,66]. Devasia et al [88] reported the first sequential RAFT polymerization to prepare block copolymers of A c c e p t e d M a n u s c r i p t 25 polymerization.…”
Section: Block Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few CRP techniques can properly mediate the radical polymerization of NVCL, including reversible additionfragmentation chain transfer (RAFT) [16][17][18][19][88][89][90][91][92][93][94][95], a combination of ring-opening polymerization (ROP) and RAFT [96,97], atom transfer radical polymerization (ATRP) [98], and Cobalt mediated radical polymerization (CMRP) [20,29,66]. Devasia et al [88] reported the first sequential RAFT polymerization to prepare block copolymers of A c c e p t e d M a n u s c r i p t 25 polymerization.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Synthetic strategies for the preparation of poly(ε-caprolactone)-b-poly(Nvinylcaprolactam) (PCL-b-PNVCL) block copolymers[96,97,101,102].…”
mentioning
confidence: 99%
“…Also, polymerization of N-VCL with the macromolecular design via interchange of xanthates (MADIX) technique has been reported. [35][36][37] MADIX polymerization resulted in much better control over molecular mass than the ATRP technique. 36 Surface-initiated polymerization of N-VCL by means of controlled radical polymerization methods has not received attention so far.…”
mentioning
confidence: 95%
“…During heating, the intensity keeps constant within the temperature range from 20 to 36 C but starts to rapidly increase above 37 C. At the same time, the diameter of the particles decreases gradually from 400 nm at 20 C to 120 nm at 37 C. It should be noted that the size of the untreated particles was estimated from SEM images which method gives a higher value than light scattering. In the temperature range [37][38][39][40][41][42][43][44][45][46][47][48][49][50] C, the size increases slightly and settles to 300 nm. SCHEME 2 ATRP polymerization of N-VCL and the reaction with NaN 3 .…”
mentioning
confidence: 99%
“…Como exemplos de PHAs têm-se o poli(3-hidroxibutirato) (PHB) e seus copolímeros com hidroxivalerato (PHBHV) (SIMIONI et al, 2008). Os polímeros sintéticos mais empregados são o poli(ácido lático) (PLA) (YANG et al, 2011), poli(ácido glicólico) (PLGA) (ACHARYA et al, 2011), poli(etileno glicol) (PEG) (HUTANU et al, 2014;XIAO et al, 2011), a poli(ɛ-caprolactona) (PCL) (YU et al, 2012) e a poli(N-vinilcaprolactama que têm atraído grande interesse de pesquisadores recentemente (CORTEZ-LEMUS; LICEA-CLAVERIE, 2015;.…”
unclassified